Practical application of Python in solving systems of linear and nonlinear equations - Qudratova Gulshoda Shodmonkulovna (Zien Journals, 2023)
The article studied methods for writing programs that solve scientific problems in the Python programming language
Keywords: Python; numerical method; scipy